PERUBAHAN SOSIAL-KEAGAMAAN DI KOMUNITAS AHMADIYAH DUSUN KRUCIL KECAMATAN BAWANG KABUPATEN BANJARNEGARA - Fahri Hidayat (IAIN Purwokerto, 2019)
This article examines beliefs, history, social changes that occur in the Ahmadiyya community in Krucil hamlet Banjarnegara. This hamlet is an area inhabited by majority of Ahmadiyah followers, as well as being a center of activity for Ahmadiyya Jama'at in Central Java. The results of this study explain that regardless of the true or false ideology that is believed, but the belief in an ideology/religious understanding can encourage social change. In the case of the community in Krucil Hamlet, the social changes that occurred were predominantly influenced by the religious ideology that was believed. Keywords: Ahmadiyah, Socio-religious, Dusun Krucil.